Heterogeneity of Cortical Lesion Susceptibility Mapping in Multiple Sclerosis - Castellaro, M. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Quantitative susceptibility mapping has been used to characterize iron and myelin content in the deep gray matter of patients with multiple sclerosis. Our aim was to characterize the susceptibility mapping of cortical lesions in patients with MS and compare it with neuropathologic observations. MATERIALS AND METHODS: The pattern of microglial activation was studied in postmortem brain tissues from 16 patients with secondary-progressive MS and 5 age-matched controls. Thirty-six patients with MS underwent 3T MR imaging, including 3D double inversion recovery and 3D-echo-planar SWI. RESULTS: Neuropathologic analysis revealed the presence of an intense band of microglia activation close to the pial membrane in subpial cortical lesions or to the WM border of leukocortical cortical lesions. The quantitative susceptibility mapping analysis revealed 131 cortical lesions classified as hyperintense; 33, as isointense; and 84, as hypointense. Quantitative susceptibility mapping hyperintensity edge found in the proximity of the pial surface or at the white matter/gray matter interface in some of the quantitative susceptibility mapping–hyperintense cortical lesions accurately mirrors the microglia activation observed in the neuropathology analysis. CONCLUSIONS: Cortical lesion susceptibility maps are highly heterogeneous, even at individual levels. Quantitative susceptibility mapping hyperintensity edge found in proximity to the pial surface might be due to the subpial gradient of microglial activation.